Thermodynamic analysis of waste heat recovery using Organic Rankine Cycle (ORC) for a two-stroke low speed marine Diesel engine in IMO Tier II and Tier III operation. (15th September 2019) - Lion, Simone; Taccani, Rodolfo; Vlaskos, Ioannis; Scrocco, Pietro; Vouvakos, Xenakis; Kaiktsis, Lambros
Abstract: In the present study, a complete thermodynamic model of a two-stroke, low speed, 13.6 MW marine Diesel engine of Winterthur Gas & Diesel has been developed using the engine simulation software Ricardo WAVE. The model has been first validated against experimental data. A Low Pressure (LP) EGR architecture has then been implemented in order to assess the engine performance in the frame of the IMO Tier III regulations. The computational results have been used as inputs to a thermodynamic process simulation model, developed in Engineering Equation Solver, able to quantify the performance of different Organic Rankine Cycle (ORC) architectures and working fluids, with the scope of obtaining the maximum net power output for all engine operating points considered. The outcome of the present study is that, through the combined use of innovative emission reduction strategies, such as LP EGR, and waste heat recovery systems, such as ORC, it is possible to develop marine Diesel engines which exhibit fuel consumption levels comparable to those of Tier II operation, at substantially reduced levels of pollutant emissions. A preliminary economic analysis has yielded annual financial savings in fuel cost of the order of 5% for operation with ORC, as compared to operation without ORC. Highlights: A two-stroke low speed ship Diesel engine has been simulated. A LP EGR emission reduction architecture has been modelled and evaluated. Several ORC architectures have been modelled and thermodynamically assessed. The combined engine-ORC system fuel consumption benefit has been quantified. A preliminary annual fuel cost saving analysis has been carried out.